Impact of Co-operation and Competences on the Innovating Behavior: A Micro-econometric Study of the French Firms. - Mohamed Karim Kefi (International Journal of Economics and Financial Issues, 2012)
The analysis of innovative behavior is suited to several ways of comments. The economic literature emphasizes, in many cases, different effects of innovation in products and processes on international trade, growth, employment and the firms performance. However, little knowledge about the impacts of competence and inter-firms co-operation on the innovative behavior (products or/and processes). According to a more empirical approach, incorporating both the “cooperation’s effect” and “competence’s effect”, we have tried to explain such innovative behavior. The results which led this article can qualify some gains with regard to incentives for innovation on the one hand, and put into perspective a new approach to innovative behavior (cooperation / competence, which by joint analysis of co-operation agreements and skills can explain the development of these innovative behaviours, on the other. Based on our results and on limits and extensions associated with them, it appears that the innovative behavior of the firm (products, processes, or products & processes) is not only a reflection of motivation strategic businesses, but also their types of skills underlying any engagement in a co-operation agreement. Thus, innovation policy unveils partly the interest shown by business groups (government, university) with respect to the co-operation agreements in R & D.